2016
DOI: 10.1080/10509674.2016.1181132
|View full text |Cite
|
Sign up to set email alerts
|

Secondary trauma among community corrections staff: An exploratory study

Abstract: This article explores the demographic factors, background characteristics, and workplace perceptions that predict secondary trauma among probation/parole and residential officers. Our results indicate that probation/parole officers were more likely to report secondary trauma than residential officers. Additionally, we found that officers who reported better health, better job training, and fewer contact hours with offenders were also less likely to report secondary trauma. These results fill a muchneeded gap i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 26 publications
2
50
0
Order By: Relevance
“…It is clear that exposure to traumatic events represents a significant occupational hazard for prison mental health nurses and correctional officers and on line with previous studies in different settings (Malkina-Pykh, 2017;Rhineberger-Dunn et al, 2016;Sinclair et al, 2017;Sorenson et al, 2016), we found that experiencing traumatic events may have a negative impact on burnout, compassion satisfaction, and compassion fatigue. Given exposure to traumatic events appears to be linked to reduced staff wellbeing, they should not be seen as acceptable and dismissed as part of working in the prison environment and efforts are needed to address aspects of the prison environment which lead to patients engaging in deliberate self-harm and suicide and being verbally and physically abusive to staff.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is clear that exposure to traumatic events represents a significant occupational hazard for prison mental health nurses and correctional officers and on line with previous studies in different settings (Malkina-Pykh, 2017;Rhineberger-Dunn et al, 2016;Sinclair et al, 2017;Sorenson et al, 2016), we found that experiencing traumatic events may have a negative impact on burnout, compassion satisfaction, and compassion fatigue. Given exposure to traumatic events appears to be linked to reduced staff wellbeing, they should not be seen as acceptable and dismissed as part of working in the prison environment and efforts are needed to address aspects of the prison environment which lead to patients engaging in deliberate self-harm and suicide and being verbally and physically abusive to staff.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies of burnout, compassion fatigue and compassion satisfaction, including with community correctional staff (Rhineberger-Dunn, Mack, & Baker, 2016), correctional psychologists (Malkina-pykh, 2017) and other mental health professionals (Morse, Salyers, Rollins, Monroe-DeVita, & Pfahler, 2012), have identified variables that confer risk in a range of settings and a number of these factors are present in the prison setting (e.g. caring for traumatized individuals, lack of environmental control, role ambiguity, understaffing, and confrontations with patients).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the community correctional literature (Goldhill, 2019;Rhineberger-Dunn et al, 2016;Severson and Pettus-Davis, 2013), the primary operational stressor identified by PPOs was potential secondary trauma arising from exposure to details about the actions or personal histories of those under their supervision and victims. Respondents regularly identified the stress that secondary exposure could cause.…”
Section: Operational Stressors: Exposure To Pptes and Secondary Traumamentioning
confidence: 68%
“…Threat of harm has not been included as much in either the institutional correctional or community corrections research as a predictor of job stress or job satisfaction. However, it has been included in research on community corrections staff and found to be a predictor of secondary trauma (Lewis et al, 2013;Rhineberger-Dunn, Mack, & Baker, 2016) and burnout (Lewis et al, 2013).…”
Section: Job Characteristicsmentioning
confidence: 99%